Better before worse trajectories in food systems? An investigation of synergies and trade-offs through climate-smart agriculture and system dynamics - Jagustović, Renata; Papachristos, George; Zougmoré, Robert B.; Kotir, Julius H; Kessler, Aad; Ouédraogo, Mathieu; Ritsema, Coen J.; Dittmer, Kyle M (Elsevier, 2021)
CONTEXT Food systems face multiple challenges simultaneously: provision to a growing population, adaptation to more extreme and frequent climate change risks, and reduction of their considerable greenhouse gas (GHG) emissions. Food system interventions and policies give rise to synergies and trade-offs that emerge over time due to the dynamic nature and interconnections of system elements. Analysis of an entire food system is necessary to identify synergies that bring simultaneous benefits and mitigate trade-offs, both short- and long-term.